Evidence for genetic and behavioral adaptations in the ontogeny of prehistoric hunter-gatherer limb robusticity - Osipov, Benjamin; Temple, Daniel; Cowgill, Libby; Harrington, Leslie; Bazaliiskii, Vladimir; Weber, Andrzej (HAL CCSD, 2016)
International audience Biomechanical analyses of past populations have primarily focused on adults and interpreted variation inlimb bone robusticity as indicative of differences in behavior. However, prior to skeletal maturity largechanges occur in limb bone robusticity and shape. During ontogeny, the accrual of bone is regulated bydifferences in genetics and nutrition as well as mechanical loading. We consider how long bonerobusticity changes from birth to young adulthood in order to understand when population differencesappear during development and why this occurs.We analyzed the femoral and humeral midshafts of four prehistoric hunter-gatherer skeletal samplesfrom four regions: Cis-Baikal, Siberia, Point Hope, Alaska, the central Japanese coast, and the South AfricanCape. Some statistically significant differences between populations manifest at birth or soon after.Some of this systemic patterning likely reflects adaptation of body shape to climate. Later Stone AgeSouth Africans also appear to demonstrate low limb rigidity residuals as a result of growth towards aunique body type. Differentiation between populations also increases with age, pointing to functionaladaptation as a result of behavioral differences. This proves largely concordant with other lines of evidencefor differing levels of terrestrial and aquatic mobility in these populations.